Modified Strut Effectiveness Factor for FRP-Reinforced Concrete Deep Beams - N. Hanoon, Ammar; R. Al Zaidee, Salah; Sahib Banyhussan, Qais; A. Abdulhameed, Ali (International Journal of Engineering and Technology, 2018)
A few examinations have endeavored to assess a definitive shear quality of a fiber fortified polymer (FRP)- strengthened solid shallow shafts. Be that as it may, need data announced for examining the solid profound pillars strengthened with FRP bars. The majority of these investigations don't think about the blend of the rigidity of both FRP support and cement. This examination builds up a basic swagger adequacy factor model to evaluate the referenced issue. Two sorts of disappointment modes; concrete part and pulverizing disappointment modes were examined. Protection from corner to corner part is chiefly given by the longitudinal FRP support, steel shear fortification, and cement rigidity. The proposed model has been confirmed utilizing an aggregate of 45 databases gathered from writing. Results show that the proposed model can evaluate a definitive shear quality. Structure of trial (DOE) programming was used to examine the impact of different parameter esteems on a definitive shear quality limit. The outcomes demonstrate that the shear range to powerful profundity proportion has the most astounding impact contrasted and alternate parameters.Â Â Â